Impact of the TLR4 agonist BECC438 on a novel vaccine formulation against Shigella spp. - Lu, Ti; Das, Sayan; Howlader, Debaki R.; Jain, Akshay; Hu, Gang; Dietz, Zackary K.; Zheng, Qi; Ratnakaram, Siva Sai Kumar; Whittier, Sean K.; Varisco, David J.; Ernst, Robert K.; Picking, William D.; et al. (Frontiers in Immunology, 2023)
Shigellosis (bacillary dysentery) is a severe gastrointestinal infection with a global incidence of 90 million cases annually. Despite the severity of this disease, there is currently no licensed vaccine against shigellosis. Shigella's primary virulence factor is its type III secretion system (T3SS), which is a specialized nanomachine used to manipulate host cells. A fusion of T3SS injectisome needle tip protein IpaD and translocator protein IpaB, termed DBF, when admixed with the mucosal adjuvant double-mutant labile toxin (dmLT) from enterotoxigenic E. coli was protective using a murine pulmonary model. To facilitate production of this platform, a recombinant protein that consisted of LTA-1, the active moiety of dmLT, and DBF were genetically fused, resulting in L-DBF which showed improved protection against Shigella challenge. To extrapolate this protection from mice to humans, we modified the formulation to provide for a multivalent presentation with the addition of an adjuvant approved for use in human vaccines. Here, we show that L-DBF formulated (admix) with a newly developed TLR4 agonist called BECC438 (a detoxified lipid A analogue identified as Bacterial Enzymatic Combinatorial Chemistry candidate #438), formulated as an oil-in-water emulsion has a very high protective efficacy at low antigen doses against lethal Shigella challenge in our mouse model. Optimal protection was observed when this formulation was introduced at a mucosal site (intranasally). When the formulation was then evaluated for the immune response it elicits, protection appears to correlate with high IFN-γ and IL-17 secretion from mucosal site lymphocytes.